Conditions of Agricultural Growth. - Boserup, Ester (Taylor and Francis, 2013)
Investigating the process of agrarian change, this book analyzes costs and productivity under the main systems of primitive agriculture. The conclusion is that technical, economic and social changes are unlikely to take place within primitive agriculture unless the rural community concerned is exposed to the pressure of population growth: a conclusion that is in sharp contrast to generally accepted ideas. The themes in the book are central to the discussion of the problems of population explosion and the world's undernourished peoples.